Study of Urban Milk Supply Schemes - Planning Commission (Planning Commission, 1974)
The evaluation of Urban Milk Supply Schemes was taken up in 1970-71 on the request of the Planning Commission. This study covered the programme of dairying in 12 States and involved a detailed study of 14 milk supply schemes of which 10 were in the public sector, 3 in the cooperative sector and 1 was being run by the Municipal Corporation, Ahmadabad. The detailed data collected for analysis pertained to the years 1967-68 to 1969-70, but for the sake of comparison, certain data was also collected for the first full year of working of selected schemes.
Programme Evaluation Organisation Planning Commission Government of India